Total stations versus GPS systems - Akatova, D. S. (My University, 2021)
The development of geodesy as a science and construction in general, requires the use of modern technologies and equipment that save resources and increase efficiency. Over the past few years, geodetic equipment has been rapidly improved and modernized, their functional features have significantly expanded, technical characteristics have improved. It is proved that modern satellite technologies in combination with computerization have become a real alternative to traditional types of geodetic measurements.
Keywords: geodesy; satellite technologies; GPS system